2014
DOI: 10.1016/j.bcp.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro metabolism of phospho-sulindac amide, a novel potential anticancer agent

Abstract: Phospho-sulindac amide (PSA) is a novel potential anti-cancer and anti-inflammatory agent. Here we report the metabolism of PSA in vitro. PSA was rapidly hydroxylated at its butane-phosphate moiety to form two di-hydroxyl-PSA and four mono-hydroxyl-PSA metabolites in mouse and human liver microsomes. PSA also can be oxidized or reduced at its sulindac moiety to form PSA sulfone and PSA sulfide, respectively. PSA was mono-hydroxylated and cleared more rapidly in mouse liver microsomes than in human liver micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Members of the FMO gene family display distinct temporal-, tissue-, and speciesspecific expression patterns (Klick and Hines, 2007). Typical FMO substrates include trimethylamine, catecholamines (Türkano glu Özçelik et al, 2013), nicotine (Bloom et al, 2013), imipramine (Wagmann et al, 2016), prothipendyl (Krueger and Williams, 2005), amitriptyline (Krueger and Williams, 2005), phospho-sulindac amide (Xie et al, 2014), benzydamine (BZD) (Taniguchi-Takizawa et al, 2015), ranitidine (Overby et al, 1997), tamoxifen (Parte and Kupfer, 2005), clozapine (Tugnait et al, 1997), diphenhydramine (Cruciani et al, 2014), and amphetamine and methamphetamine (Cashman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the FMO gene family display distinct temporal-, tissue-, and speciesspecific expression patterns (Klick and Hines, 2007). Typical FMO substrates include trimethylamine, catecholamines (Türkano glu Özçelik et al, 2013), nicotine (Bloom et al, 2013), imipramine (Wagmann et al, 2016), prothipendyl (Krueger and Williams, 2005), amitriptyline (Krueger and Williams, 2005), phospho-sulindac amide (Xie et al, 2014), benzydamine (BZD) (Taniguchi-Takizawa et al, 2015), ranitidine (Overby et al, 1997), tamoxifen (Parte and Kupfer, 2005), clozapine (Tugnait et al, 1997), diphenhydramine (Cruciani et al, 2014), and amphetamine and methamphetamine (Cashman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This limited stability decreases their efficacy and increases their toxicity. To overcome this problem, phospho-sulindac amide (PSA, IV-7 in Figure 4) 307 and phospho-ibuprofen amide (PIA, IV-8 in Figure 4) 290 were synthesized as metabolically stable analogs of the phosphosulindac (P-S, OXT-328, IV-1 in Figure 4) and phospho- ibuprofen (MDC-917, IV-2 in Figure 4), respectively. Furthermore, phospho-ibuprofen amide (PIA) was encapsulated into liposomes to improve its pharmacokinetic profile.…”
Section: Development Of Nsaid Analogs and Theirmentioning
confidence: 99%
“…In this context, several NSAID analogs mentioned previously have demonstrated potent antitumoral activity. Particularly, modifications in the NSAIDs to make them able to release antioncogenic agents such as H 2 S and NO (Figures –) as well as phospho-NSAIDs (Figure ) have been widely studied. Especially, HS- and HSNO-NSAIDs and phosphoramide-modified NSAIDs have been shown to improve the antitumoral activity and limit gastrointestinal side effects of NSAIDs.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Further investigations with mouse and human liver microsomes showed that phospho-sulindac amide is oxidized or reduced. The oxidation and reduction reactions were observed with the formation of sulfone and sulfide derivatives of phospho-sulindac amide respectively (6). The metabolic pathway from sulfoxide to sulphide has been used on a common non-steroidal anti-inflammatory pro-drug, Sulindac.…”
mentioning
confidence: 99%